A measuring method for large antenna assembly using laser and vision guiding technology. (October 2016) - Peng, Gaoliang; Sun, Yu; Han, Rui; Li, Chuanhao; Liu, Shaohui
Highlights: We propose a novel measuring system for mobile radar automated assembly. The measuring system decomposes the measurement task in each assembly step. A new vision based method is utilized to assist quick collimation over large space. Laser meters and PSD sensor is used to precisely measure the position and orientation. The measuring method taking into account the operation conditions and the environmental influences. Abstract: In this paper a new conception of a measuring method is proposed to assist precision automatic assembly of large radar antenna. Different from conventional 6-DOF tracking methods, the measuring system decomposes the measurement task into several independent steps. The measuring system consists of a camera, two laser distance meters, two position sensitive detectors (PSD) and an inclination angle sensor. The camera is adopted to guide antenna position and orientation adjustment over a large space. Laser meters and PSD sensor is used to precisely measure the position and orientation of radar antenna. To improve the practicability of measuring system, a robust vision measurement method is proposed. The mathematical models and practical calibration methods for measurement are elaborated. The preliminary experimental results agree with the methods currently being used for orientation and position measurement. The measuring method provides an alternative choice for the metrology in precision assembly. By using the method proposed in this paper, the measuring system can achieve a measurement accuracy of approximately 1 mm, which meets the accuracy requirement of large radar antenna automatic assembly application. Besides, the measuring method provides an alternative solution for large scale metrology which take the environmental impact into account.